Optimal. Leaf size=19 \[ 2+x+\left (-2+e^{e^{e^{3+x}}}+x\right )^2+\log (5) \]
________________________________________________________________________________________
Rubi [A] time = 0.07, antiderivative size = 34, normalized size of antiderivative = 1.79, number of steps used = 5, number of rules used = 3, integrand size = 54, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.056, Rules used = {2282, 2194, 2288} \begin {gather*} x^2-3 x+e^{2 e^{e^{x+3}}}-2 e^{e^{e^{x+3}}} (2-x) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 2194
Rule 2282
Rule 2288
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=-3 x+x^2+2 \int e^{3+2 e^{e^{3+x}}+e^{3+x}+x} \, dx+\int e^{e^{e^{3+x}}} \left (2+e^{3+e^{3+x}+x} (-4+2 x)\right ) \, dx\\ &=-2 e^{e^{e^{3+x}}} (2-x)-3 x+x^2+2 \operatorname {Subst}\left (\int e^{3+2 e^{e^3 x}+e^3 x} \, dx,x,e^x\right )\\ &=-2 e^{e^{e^{3+x}}} (2-x)-3 x+x^2+\frac {2 \operatorname {Subst}\left (\int e^{3+2 x} \, dx,x,e^{e^{3+x}}\right )}{e^3}\\ &=e^{2 e^{e^{3+x}}}-2 e^{e^{e^{3+x}}} (2-x)-3 x+x^2\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.07, size = 32, normalized size = 1.68 \begin {gather*} e^{2 e^{e^{3+x}}}+2 e^{e^{e^{3+x}}} (-2+x)-3 x+x^2 \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.92, size = 26, normalized size = 1.37 \begin {gather*} x^{2} + 2 \, {\left (x - 2\right )} e^{\left (e^{\left (e^{\left (x + 3\right )}\right )}\right )} - 3 \, x + e^{\left (2 \, e^{\left (e^{\left (x + 3\right )}\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [F] time = 0.00, size = 0, normalized size = 0.00 \begin {gather*} \int 2 \, {\left ({\left (x - 2\right )} e^{\left (x + e^{\left (x + 3\right )} + 3\right )} + 1\right )} e^{\left (e^{\left (e^{\left (x + 3\right )}\right )}\right )} + 2 \, x + 2 \, e^{\left (x + e^{\left (x + 3\right )} + 2 \, e^{\left (e^{\left (x + 3\right )}\right )} + 3\right )} - 3\,{d x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.08, size = 28, normalized size = 1.47
method | result | size |
risch | \({\mathrm e}^{2 \,{\mathrm e}^{{\mathrm e}^{3+x}}}+\left (2 x -4\right ) {\mathrm e}^{{\mathrm e}^{{\mathrm e}^{3+x}}}+x^{2}-3 x\) | \(28\) |
default | \(-3 x +2 x \,{\mathrm e}^{{\mathrm e}^{{\mathrm e}^{3+x}}}-4 \,{\mathrm e}^{{\mathrm e}^{{\mathrm e}^{3+x}}}+x^{2}+{\mathrm e}^{2 \,{\mathrm e}^{{\mathrm e}^{3+x}}}\) | \(33\) |
norman | \(-3 x +2 x \,{\mathrm e}^{{\mathrm e}^{{\mathrm e}^{3+x}}}-4 \,{\mathrm e}^{{\mathrm e}^{{\mathrm e}^{3+x}}}+x^{2}+{\mathrm e}^{2 \,{\mathrm e}^{{\mathrm e}^{3+x}}}\) | \(33\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.36, size = 26, normalized size = 1.37 \begin {gather*} x^{2} + 2 \, {\left (x - 2\right )} e^{\left (e^{\left (e^{\left (x + 3\right )}\right )}\right )} - 3 \, x + e^{\left (2 \, e^{\left (e^{\left (x + 3\right )}\right )}\right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.10, size = 35, normalized size = 1.84 \begin {gather*} {\mathrm {e}}^{2\,{\mathrm {e}}^{{\mathrm {e}}^3\,{\mathrm {e}}^x}}-4\,{\mathrm {e}}^{{\mathrm {e}}^{{\mathrm {e}}^3\,{\mathrm {e}}^x}}-3\,x+2\,x\,{\mathrm {e}}^{{\mathrm {e}}^{{\mathrm {e}}^3\,{\mathrm {e}}^x}}+x^2 \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 3.67, size = 29, normalized size = 1.53 \begin {gather*} x^{2} - 3 x + \left (2 x - 4\right ) e^{e^{e^{x + 3}}} + e^{2 e^{e^{x + 3}}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________